Naturally ventilated buildings : buildings for the senses, economy and society - Clements-Croome, Derek (E & FN Spon, 1997)
While there are many historical examples of successful naturally ventilated buildings, standards for indoor climate have tended to emphasise active, mechanical airflow systems rather than passive natural systems. Despite its importance, knowledge.